P28 A comparison of daily physical activity between adults with severe asthma and healthy controls. (12th November 2019) - Neale, J; Orme, M; Chantrell, S; Majd, S; Bradding, P; Singh, SJ; Green, RH; Evans, RA
Abstract : Introduction: Current WHO physical activity guidelines recommend adults accumulate ≥150 minutes per week of moderate intensity activity in bouts of ≥10 minutes. We aimed to compare daily physical activity levels and intensity of physical activity between adults with severe asthma and healthy controls. Methods: Adults with severe asthma, defined by step 4/5 of the BTS/SIGN guidelines, under the care of a difficult asthma service at a tertiary centre, and age and sex-matched health controls were recruited. Age, gender, smoking status, and medication were recorded, and BMI calculated. Daily physical activity was measured for seven days using a SenseWear Pro-3armband triaxial accelerometer. Adequate wear time was defined as ≥eight hours per day for a valid day with a minimum of four valid days. Steps, stationary time, time spent in moderate-vigorous activity (MVPA) and MVPA in ≥10 minute bouts were analysed adjusted for wear time. Analysis of co-variance (ANCOVA) was used to adjust for covariates. Results: 48 people with severe asthma (35% male, mean [SD] age 55 [13] years, 25% ex-smokers, 4% current smokers, 50% prescribed oral steroids) and 48 age and sex-matched healthy participants (29% ex-smokers, 0 current smokers) completed the study. Mean [SD] BMI was higher for patients with severe asthma (33.0 [6.7] kg/m 2 ) compared to healthy participants (26.4 [4.4]) kg/m 2 ), p<0.001. Daily wear time for patients with severe asthma (mean [SD] 772 [108] min) was lower compared to healthy participants (826 [96] min), p=0.011. Figure 1 shows the physical activity levels for patients with severe asthma and healthy participants. After adjusting for BMI and monitor wear time, steps per day and time spent in ≥10 minute bouts of MVPA were lower for people with severe asthma compared to healthy participants, p=0.009 and p=0.012, respectively. However, there was no difference in stationary time between the two groups, p=0.296. Conclusion: Patients with severe asthma perform fewer steps and fewer 10 minute bouts of MVPA per day compared to their healthy peers, whereas time spent stationary was similar. Advice and interventions to increase physical activity in people with severe asthma should target MVPA.